The Children Character Improvement through Painting Activities in the Art School I Wayan Gama Painting School - Suda, I Ketut (International Research Journal of Management, IT & Social Sciences, 2017)
The present study was intended to study the process of children character improving through painting activities, in an art school namely "I Wayan Gama Painting School" in Desa Keliki, Tegallalang Sub-District, Gianyar Regency, Bali Province. In term of this was interesting due to in the midst of the various economic activities done by their parents in the family, it was occurred the children character education to be neglected...